(2bx+9x+4a)-(4bx-a)+(3b+a)=

Simple and best practice solution for (2bx+9x+4a)-(4bx-a)+(3b+a)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2bx+9x+4a)-(4bx-a)+(3b+a)= equation:


Simplifying
(2bx + 9x + 4a) + -1(4bx + -1a) + (3b + a) = 0

Reorder the terms:
(4a + 2bx + 9x) + -1(4bx + -1a) + (3b + a) = 0

Remove parenthesis around (4a + 2bx + 9x)
4a + 2bx + 9x + -1(4bx + -1a) + (3b + a) = 0

Reorder the terms:
4a + 2bx + 9x + -1(-1a + 4bx) + (3b + a) = 0
4a + 2bx + 9x + (-1a * -1 + 4bx * -1) + (3b + a) = 0
4a + 2bx + 9x + (1a + -4bx) + (3b + a) = 0

Reorder the terms:
4a + 2bx + 9x + 1a + -4bx + (a + 3b) = 0

Remove parenthesis around (a + 3b)
4a + 2bx + 9x + 1a + -4bx + a + 3b = 0

Reorder the terms:
4a + 1a + a + 3b + 2bx + -4bx + 9x = 0

Combine like terms: 4a + 1a = 5a
5a + a + 3b + 2bx + -4bx + 9x = 0

Combine like terms: 5a + a = 6a
6a + 3b + 2bx + -4bx + 9x = 0

Combine like terms: 2bx + -4bx = -2bx
6a + 3b + -2bx + 9x = 0

Solving
6a + 3b + -2bx + 9x = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3b' to each side of the equation.
6a + 3b + -2bx + -3b + 9x = 0 + -3b

Reorder the terms:
6a + 3b + -3b + -2bx + 9x = 0 + -3b

Combine like terms: 3b + -3b = 0
6a + 0 + -2bx + 9x = 0 + -3b
6a + -2bx + 9x = 0 + -3b
Remove the zero:
6a + -2bx + 9x = -3b

Add '2bx' to each side of the equation.
6a + -2bx + 2bx + 9x = -3b + 2bx

Combine like terms: -2bx + 2bx = 0
6a + 0 + 9x = -3b + 2bx
6a + 9x = -3b + 2bx

Add '-9x' to each side of the equation.
6a + 9x + -9x = -3b + 2bx + -9x

Combine like terms: 9x + -9x = 0
6a + 0 = -3b + 2bx + -9x
6a = -3b + 2bx + -9x

Divide each side by '6'.
a = -0.5b + 0.3333333333bx + -1.5x

Simplifying
a = -0.5b + 0.3333333333bx + -1.5x

See similar equations:

| 6(3x-5)=3(6x+6) | | -2(q-4)=3q+12 | | 8(3a+7c)-6(2a+6c)= | | (2a^2b+7ab^2)+(3ab^2-2a^2b)= | | 8+2s-7=7s+3-4s | | -(3y+1)-(-2y-4)=-1 | | 3(x-2)(x+1)=0 | | -2y+6=20 | | 4z-7=5(5z-3) | | (5b-1)(6b-3)= | | 2x+20=304 | | -6x-(9y+(5x-(-2y-b))-(2b+a))= | | 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= |

Equations solver categories